Health-related quality of life in patients with narcolepsy types 1 and 2 from a Sleep Center in Brazil - CREMASCHI, Renata Carvalho; HIROTSU, Camila; TUFIK, Sergio; COELHO, Fernando Morgadinho (Arquivos de Neuro-Psiquiatria, 2020)
Introduction: Narcolepsy patients have higher prevalence of comorbidities, such as obesity, depression, and pain. Narcolepsy symptoms and concomitant medical conditions can impact the daily activities of patients. The objective of this study is to describe the quality of life in a sample of patients with narcolepsy, and the influence of the nutritional status in health domains. Methods: At Unifesp, two groups of 33 patients (narcolepsy types 1 and 2 meeting 2014 criteria, concerning hypocretin-1) and 33 controls without sleepiness, matched by age and sex, filled out the SF-36. Results: Narcolepsy groups, regardless of their nutritional status, had significantly lower scores in all domains, compared to controls, mainly in Role-physical, Role-emotional, and Energy/Fatigue. Role-physical score was lower in type 1 than in type 2 and controls (37.8±1.0 vs. 50.0±1.2 vs. 85.6±1.6; p<0.0001). Obese with type 2 narcolepsy scored lower than type 1 in physical scales. Conclusion: In a Sleep Center in São Paulo, Brazil, physical and mental health were impaired in narcolepsy types 1 and 2. The first report of the poor health status in Brazilians with narcolepsy type 2 suggests that obesity negatively affects physical domains.
Keywords: Narcolepsy; Hypocretin-1; Quality of Life; Obesity